Rapid economic evaluation technology for oil and gas development projects in Africa. Issue 1 (February 2021) - Zou, Qian; Wang, Keming; Fa, Guifang; Yin, Xiuling; Peng, Min
Abstract: Africa is a key area for overseas oil and gas investment cooperation due to the low degree of oil and gas exploration and great resource potential. All oil and gas resource countries have certain common characteristics in contract modes, fiscal and tax terms, economic conditions, infrastructure and bidding methods. A theoretical system of rapid economic evaluation technology suitable for the characteristics of Africa can be established to provide the methods and basis for investment decisions of oil and gas development projects in Africa. In this paper, on the basis of a systematic study on oil contract modes in Africa and the legal terms, sales market, actual operations and evaluation and prediction parameters to be focused on, an economic evaluation index system has been established, including analysis framework establishment, financial benefit analysis and uncertainty analysis; finally, an oil and gas development project in Africa is taken as an example to verify the above-mentioned rapid economic evaluation technology. This technology system is applicable to economic evaluation of most oil and gas development projects in Africa, covering the possible factors, scenarios and problems in the process of project evaluation, facilitating the realization of a rapid and effective economic evaluation process and the achievement of scientific and reasonable results.